Answer:
D) 2x² + 4x - 30
Step-by-step explanation:
Follow the FOIL method:
FOIL =
First
Outside
Inside
Last
...and is the order you multiply to solve:
(x + 5)(2x - 6) =
(x)(2x) = 2x²
(x)(-6) = -6x
(5)(2x) = 10x
(5)(-6) = -30
Combine like terms. Simplify:
2x² -6x + 10x - 30 = 2x² (-6x + 10x) - 30 = 2x² + 4x - 30
2x² + 4x - 30 is your answer.
~
Answer: f(x^-1) = x/5 - 3/5
Step-by-step explanation:
1. Replace f(x) with y
2. Swap the positions of x and y to make x = 5y + 3
3. Solve for y by subtracting 3 from both sides and dividing each side by 5
Answer:
12 cards is the correct answer of this questions.
<em><u>plz</u></em><em><u> </u></em><em><u>mark</u></em><em><u> my</u></em><em><u> answer</u></em><em><u> as</u></em><em><u> brainlist</u></em><em><u> plzzzz</u></em><em><u> vote</u></em><em><u> me</u></em><em><u> also</u></em>
Answer:
Step-by-step explanation:
We are asked to represent as the product of the GCF and another sum.
First of all, we will find the greatest common factor of 18 and 24.
Factors of 18: 1, 2, 3, 6, 9, 18.
Factors of 24: 1, 2, 3, 4, 6, 8, 12, 24.
We can see that greatest common factor of 18 and 24 is 6. Let us write our given expression as product.
Factor our 6:
Therefore, our required expression would be .
You dident give us a picture of it so we cant tell